Priorities and Instruments of Local Elderly Care Policies in China: Text Mining and Comparative Analysis - Li, Xiuqi; Yang, Aoyi; Yan, Han (Frontiers in Public Health, 2021)
Health care for the elderly is one of the key issues in the field of public health. In the context of global ageing, the government's policy framework for elderly care affects the development of local elderly care. The priorities and instruments of the elderly care policy are important windows for understanding the local development planning system. This paper uses a quantitative text analysis method based on text mining to analyse 3,618 provincial policies in China. Considering the pilot demonstration projects for elderly care selected by the Chinese government in recent years, this paper finds that local elderly care policies have a three-phase evolution, and the priorities in each phase are solving the legacy of transition, expanding private sector participation, and realizing the well-being of the elderly. Moreover, mature regions use more environmental policy instruments, and the most effective are financial services, regulatory systems and strategic guidance. For immature regions, it is necessary to use more core instruments on the premise of using basic instruments so that public policies can serve local development and realize the well-being of the elderly.